Potentials of plant derived products for the treatment of skin disorders - Sandeep Kumar Maurya; Sheetal Divakar; Umesh Kumar Patil (German Journal of Pharmaceuticals and Biomaterials, 2023)
The skin is the body's largest organ. The epidermis and dermis make up the skin, and their primary purpose is to defend the body from adverse environmental factors like chemicals, allergens, toxins, and bacteria. Many different types of natural products have shown promise in the treatment of skin disorders. Multiple synthetic chemicals and environmental pollution have an impact on modern human existence. Therefore, nature has provided several essential ingredients for boosting skin health and shielding skin from environmental damage. The most significant in vivo and in vitro studies on the use of different natural products in inflammatory, cancerous, and skin infection disorders and their mechanisms of action were summarised in this review. The study also highlights the potential photoprotective effects of numerous herbal ingredients. Sunburn is caused primarily by the sun's ultraviolet rays, which can also cause cancer of the skin. Herbal ingredients with sunblocking properties can prevent the penetration of harmful ultraviolet radiation. Compared to their synthetic counterparts, herbal remedies have fewer adverse effects and are just as effective in treating chronic conditions. Flavonoids, polyphenols, carotenoids (Lycopene, carotene), and phenolic acids found in herbs rich in vitamins (A, C, and E) have antioxidant properties that increase photoprotection.